A Quasi-Experimental Comparison Of Cooperative Learning And Direct Instruction For Floor Gymnastics Skill Outcomes - Puspodari; Iqbal Arifin; Wasis Himawanto (Indonesian Journal of Educational Science (IJES), 2026)
This study aimed to evaluate the effectiveness of cooperative learning and direct instruction in improving floor gymnastics skills among physical education students. A quantitative approach employing a quasi-experimental pretest–posttest control group design was used. Eighty students participated in the study and were assigned to either the Cooperative Learning group (n = 40) or the Direct Instruction group (n = 40). Floor gymnastics performance was assessed using a validated performance rubric covering four movements: Roll Backward to Handstand (RBH), Forward Handspring (FH), Front Balance (FB), and Shoulder Stand (SS). Performance was evaluated on a five-point rating scale by trained assessors, and the instrument's content validity was established through expert review by gymnastics specialists. Data were analyzed using the Wilcoxon Signed-ranks Test and the Mann–Whitney U Test. The results demonstrated significant improvements in all four floor gymnastics skills within both instructional groups (p < 0.05). Furthermore, the between-group analysis revealed that the cooperative learning group achieved significantly higher posttest performance than the direct instruction group across all four movements, with small to moderate effect sizes (p < 0.05). These findings indicate that although both instructional strategies effectively improved students' floor gymnastics performance, cooperative learning provided greater overall learning gains. Therefore, cooperative learning may be considered a more effective instructional approach for enhancing floor gymnastics skills while promoting active student participation in physical education.